1983
DOI: 10.1111/j.1440-1681.1983.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressor Effect of Moderate Alcohol Consumption in Man: A Proposed Mechanism

Abstract: Ingestion of alcohol was associated with a highly significant increase in systolic blood pressure and heart rate which occurred before the blood alcohol reached its peak concentration of 16.9 (s.e.m. = 1.1) mol/1. Drinking non-alcoholic cold liquids caused a marked but transient fall in adrenaline and a rise in noradrenaline concentration. Alcohol prevented this fall in adrenaline and led to a sustained increase in noradrenaline concentration. These changes may be implicated in the elevation of blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
(5 reference statements)
0
4
1
Order By: Relevance
“…In contrast to findings of the effect of one-time moderate alcohol consumption (0.5-0.75 g of ethanol/kg or 2 drinks) on sympathetic activity in young adults [17][18][19][20][21], we found that MODs did not have increased urinary NE levels compared with ABs. It has been suggested that alcohol-induced sympathetic activity may be dose dependent, with no effect of alcohol consumption at low level (1 drink) [21].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to findings of the effect of one-time moderate alcohol consumption (0.5-0.75 g of ethanol/kg or 2 drinks) on sympathetic activity in young adults [17][18][19][20][21], we found that MODs did not have increased urinary NE levels compared with ABs. It has been suggested that alcohol-induced sympathetic activity may be dose dependent, with no effect of alcohol consumption at low level (1 drink) [21].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have examined the effect of alcohol consumption on sympathetic activation and there are data supporting the scientific premise that alcohol consumption in young adults may be associated with increased sympathetic activation. However, studies to date have only examined the effect of a "single, one-time" binge or moderate drinking episode [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There is now good evidence for a direct pressor effect of regular alcohol consumption in man (Puddey et al 1985a). Our attempts to understand the mechanism of such an effect have so far addressed possible influences o n sympatho-adrenergic mechanisms (Ireland et al 1983), the renin-angiotensin axis (Puddey et al 1985b), membrane sodium handling (Puddey et al 1986) and calcium metabolism (Arkwright et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Older studies showed roles for the sympathetic and central nervous systems in the elevation of blood pressure that occurs in the hours following ethanol ingestion [25], as well as in cellular divalent ion dysregulation [26]. Other proposed mechanisms are detailed in Table 1.…”
Section: Mechanismsmentioning
confidence: 98%